INGLIZ TILI GRAMMATIKASINI YOSHLARGA O‘RGATISH UCHUN FOYDALI TIZIMLAR (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
his article explores modern, effective, and innovative methods of teaching English grammar. It analyzes the communicative approach, the contextual method, the use of technology, the differentiated approach, and game-based methods in grammar instruction. Alongside theoretical perspectives, the article also provides practical recommendations.